IMPROVEMENT OF WAREHOUSE LAYOUT USING DEDICATED STORAGE METHOD TO OPTIMIZE STORAGE UTILIZATION OF AUTOMOTIVE COMPONENTS AT PT XYZ - Imdam, Irma Agustiningsih; Fadlurochman, Muhammad; Sukmawati, Wilad; Marizka, Dewi Auditiya; Rangkuti, Indra Yusuf (Journal of Industrial Engineering Management, 2024)
The warehouse has a very important role in the supply chain network to distribute products to consumers. PT XYZ warehouse uses a rack system to store products before they are distributed to the production process. The problem faced is that the placement of products is scattered and irregular depending on the conditions in the field, products that come are placed in empty places which can cause the storage space to become larger so that the warehouse capacity has not been fully utilized with a utilization rate of 105% and causes a decrease in the actual warehouse capacity. It’s necessary to rearrange the placement of products in the storage location to optimize the utilization rate of storage space, with the dedicated storage method.  This method is to solve the problems that occur in the warehouse layout which includes product placement in the warehouse by placing only one type of product in one storage room. In this method, products will be stored in a fixed location so that product storage is more organized. The results of the application of the dedicated storage method obtained a storage space utilization rate of 100%, while in the existing condition it was 105% with a percentage decrease of 5%.